2022
DOI: 10.1136/bmj-2022-071752
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and corroboration of safety signals identified from the US Food and Drug Administration Adverse Event Reporting System, 2008-19: cross sectional study

Abstract: Objective To characterize potential drug safety signals identified from the US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS), from 2008 to 2019, to determine how often these signals resulted in regulatory action by the FDA and whether these actions were corroborated by published research findings or public assessments by the Sentinel Initiative. Design Cross sectional study. Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…To better understand the FDA’s pharmacovigilance efforts, in our linked study in The BMJ ,8 we characterised safety signals identified from FAERS from 2008 to 2019 and determined how often these signals resulted in FDA regulatory actions. Next, among a subset of signals from 2014 and 2015, we ascertained whether these regulatory actions were corroborated by the studies published in the medical literature or by Sentinel Initiative assessments.…”
mentioning
confidence: 99%
“…To better understand the FDA’s pharmacovigilance efforts, in our linked study in The BMJ ,8 we characterised safety signals identified from FAERS from 2008 to 2019 and determined how often these signals resulted in FDA regulatory actions. Next, among a subset of signals from 2014 and 2015, we ascertained whether these regulatory actions were corroborated by the studies published in the medical literature or by Sentinel Initiative assessments.…”
mentioning
confidence: 99%
“…In a linked paper (doi:10.1136/bmj-2022-071752), Dhodapkar and colleagues analysed 12 years of safety signals identified within the US Food and Drug Administration’s Adverse Event Reporting System (FAERS) 5. They asked how often these signals resulted in regulatory actions and whether they were corroborated by additional research.…”
mentioning
confidence: 99%
“…Dhodapkar and colleagues assessed the role and impact of safety signals from the US Food and Drug Administration’s Adverse Event Reporting System (FAERS) database on subsequent regulatory actions by the administration 1. Spontaneous reporting systems and analyses of aggregated cases in databases such as FAERS are a cornerstone in generating post-marketing safety signals.…”
mentioning
confidence: 99%